Post a New Question


posted by on .

Use the product rule to calculate the derivative.
x = 4 ,

h (x) = (x^(-1/2) + 7x)(9 - x^-1)

very weird.. i know how to do it, i used product rule and got an answer in decimal but the website is not accepting it. Can any one help me?...

  • CALCULUS - ,

    Let's multiply it out and not use the product rule. The answer should be the same.

    h(x) = 9x^(-1/2) -x^(-3/2) +63x -7
    dh/dx = -(9/2)x^(-3/2) +(3/2)x^(-5/2) + 63

    dh/dx @ x=4 = (-9/2)(1/8) +(3/2)(1/32)+63
    = -9/16 +3/64 +63

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question